1999
DOI: 10.1074/jbc.274.36.25393
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Vanadate with the Cloned Beta Cell KATP Channel

Abstract: Vanadate is used as a tool to trap magnesium nucleotides in the catalytic site of ATPases. However, it has also been reported to activate ATP-sensitive potassium (K ATP ) channels in the absence of nucleotides. K ATP channels comprise Kir6.2 and sulfonylurea receptor subunits (SUR1 in pancreatic beta cells, SUR2A in cardiac and skeletal muscle, and SUR2B in smooth muscle). We explored the effect of vanadate (2 mM ATP-sensitive potassium (K ATP )1 channels are found in a variety of tissues where they couple ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Szabó et al (57) has reported that the photoaffinity labeling of NBF2 of CFTR increases in the presence of orthovanadate, whereas NBF1 of CFTR binds 8-azido-[␣-32 P]ATP stably similar to SURx. However, we observed no vanadate-induced nucleotide trapping in any NBFs of SURx subtypes (data not shown), in agreement with the results of experiments demonstrating that orthovanadate does not influence K ATP channel activity (41,58). This suggests that the mechanism of ATP hydrolysis at NBF2 of SURx is different from other ABC proteins.…”
Section: Discussionsupporting
confidence: 81%
“…Szabó et al (57) has reported that the photoaffinity labeling of NBF2 of CFTR increases in the presence of orthovanadate, whereas NBF1 of CFTR binds 8-azido-[␣-32 P]ATP stably similar to SURx. However, we observed no vanadate-induced nucleotide trapping in any NBFs of SURx subtypes (data not shown), in agreement with the results of experiments demonstrating that orthovanadate does not influence K ATP channel activity (41,58). This suggests that the mechanism of ATP hydrolysis at NBF2 of SURx is different from other ABC proteins.…”
Section: Discussionsupporting
confidence: 81%
“…These results suggest that the catalytic mechanism of the NBFs of SUR1 may be different from that of the NBFs of MDR1 and CFTR. This is in agreement with experiments demonstrating that orthovanadate does not influence K ATP channel activity (38,39).…”
Section: Discussionsupporting
confidence: 81%
“…Our results indicate that these different responses are mediated by the first set of transmembrane domains of SUR (TMs 1-6). It is noteworthy that this region of SUR confers the different gating kinetics of Kir6.2/SUR1 and Kir6.2/SUR2A channels (46,47).…”
Section: Resultsmentioning
confidence: 99%